Photocatalytic Degradation and Hydrogen Production of TiO2/Carbon Fiber Composite Using Bast as a Carbon Fiber Source. (3rd June 2018) - Tang, Guomei; Abas, Asim; Wang, Shanpeng
Abstract : TiO2 /carbon fiber composite is achieved by loading TiO2 nanoparticles on biomass carbon fiber, which originates from the carbonized natural bast. The carbonized process and the loading amount of TiO2 are researched in detail. It is found that the carbonized bast fiber shows robust adsorption characteristics for TiO2 nanoparticles in aqueous dispersion, and TiO2 nanoparticles with ~15 wt.% in total weight are uniformly loaded onto the fiber surface. The photocatalytic properties of TiO2 /carbon fiber composite are evaluated by photocatalytic degradation of rhodamine B and water splitting for hydrogen production. The results indicate that 90% RhB molecules could be attacked in 60 min under UV light irradiation, and the hydrogen production rate of water splitting is up to 338.51  μ mol/h. The highlight is that TiO2 /carbon fiber composite is easy to be recycled due to the incorporation of macroscopical biomass carbon fiber.